Socio-cultural and economic determinants and consequences of adolescent undernutrition and micronutrient deficiencies in LLMICs: A systematic narrative review - Madjdian, Donya S.; Azupogo, Fusta; Osendarp, Saskia J. M.; Bras, Hilde; Brouwer, Inge D. (New York Academy of Sciences, 2018)
Adolescent undernutrition is a persisting public health problem in low and lower middle income countries (LLMICs). Nutritional trajectories are complexly interrelated with socio‐cultural and economic (SCE) trajectories. However, a synthesis of the SCE determinants or consequences of undernutrition in adolescents is lacking. We undertook a narrative review of published literature to provide a narrative overview of the SCE determinants and consequences associated with undernutrition among adolescents in LLMICs. We identified 98 articles from PubMed, SCOPUS, and CAB‐Abstracts on determinants and consequences of undernutrition as defined by stunting, underweight, thinness, and micronutrient deficiencies. At the individual level, significant determinants included age, sex, birth order, religion, ethnicity, educational and literacy level, working status, and marital status. At the household level, parental education and occupation, household size and composition, income, socioeconomic status, and resources were associated with undernutrition. Only a few determinants at the community/environmental level, including residence, sanitation, school type, and seasonality, were identified. The consequences of adolescent undernutrition were mostly related to education and cognition. This review underscores the importance of the broad range of context‐specific SCE factors at several levels that influence adolescent nutritional status and shows that further research on SCE consequences of undernutrition is needed.